Pengaruh Training dan Tallent Management Terhadap Kinerja Karyawan dengan Retensi Karyawan sebagai Variabel Intervening pada Karyawan Gen Z di Kabupaten Pasuruan - Danis Novitasari; Antin Rakhmawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Training and Talent Management on Employee Performance, with Employee Retention as an intervening variable, among Generation Z employees in Pasuruan Regency. Generation Z represents a productive age group with unique characteristics and significant potential to drive company progress. Therefore, it is crucial for organizations to understand the factors that affect their performance.This research uses a quantitative approach with a survey method by distributing questionnaires to 70 respondents who are Gen Z employees in several companies in Pasuruan Regency. Data analysis was carried out using path analysis and the Sobel test to examine both direct and indirect effects between variables.The results of the study show that Training and Talent Management have a positive and significant effect on Employee Retention and Employee Performance. In addition, Employee Retention also has a significant effect on Employee Performance and mediates the relationship between Training and Talent Management and Employee Performance. This means that the better the training and talent management provided, the higher the level of retention and performance produced by Gen Z employees.The relevance of this research lies in the importance for companies to design training and talent management programs that align with the characteristics and needs of Gen Z employees in order to improve loyalty and work performance in a sustainable manner.